Simultaneous detection of microorganisms in soil suspension based on PCR amplification of bacterial 16S rRNA fragments - McGregor, D P (BioTechniques, 1996)
The effect of buffer composition on simultaneous PCR amplification of 16S rRNA gene fragments of five bacterial species was examined using a number of different buffer systems. Tris-based PCR buffers at final concentrations of 10 mM proved unreliable. However, when the final concentration of Tris was increased to 75 mM, all five samples were routinely detected. The use of other buffers, 3-[(1,1-dimethyl-2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid (AMPSO) and 3-[cyclohexylamino]-2-hydroxy-1-propanesulfonic acid (CAPSO), resulted in PCR amplification of five products even at low final concentrations (10 mM). The presence of certain proteins in the amplification reaction could overcome an inhibitory effect seen when soil suspension was present in the reaction, as might occur when testing field samples for the presence of bacteria. Bovine serum albumin was found to be the most effective additive tested in overcoming inhibition